2010
DOI: 10.1007/s00109-009-0587-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamin 2 and human diseases

Abstract: Dynamin 2 (DNM2) mutations cause autosomal dominant centronuclear myopathy, a rare form of congenital myopathy, and intermediate and axonal forms of Charcot-Marie-Tooth disease, a peripheral neuropathy. DNM2 is a large GTPase mainly involved in membrane trafficking through its function in the formation and release of nascent vesicles from biological membranes. DNM2 participates in clathrin-dependent and clathrin-independent endocytosis and intracellular membrane trafficking (from endosomes and Golgi apparatus)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
101
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 156 publications
0
101
1
1
Order By: Relevance
“…At least a part of the TTN protein is not translated in some patients with TTN-related CNM [48]. The pathomechanism of DNM2 mutations has been somewhat perplexing [50]. All DNM2 mutations are either dominant or de novo missense mutations, suggesting a potentially toxic gain-of-function effect produced by the mutations.…”
Section: What Causes It?mentioning
confidence: 99%
“…At least a part of the TTN protein is not translated in some patients with TTN-related CNM [48]. The pathomechanism of DNM2 mutations has been somewhat perplexing [50]. All DNM2 mutations are either dominant or de novo missense mutations, suggesting a potentially toxic gain-of-function effect produced by the mutations.…”
Section: What Causes It?mentioning
confidence: 99%
“…Other characteristics include a relative increase in the number of type I fibers, hypertrophy of these fibers, and the presence of sarcoplasmic strands distributed radially around the central nuclei. In 2005, Bitoun et al (2) reported the identification of four mutations in the DNM2 (dynamin 2) gene in patients with autosomal dominant CNM, and an additional seven mutations have since been identified (3,4). DNM2 is a ubiquitously expressed ϳ100-kDa GTPase that assembles into helical polymers around the necks of vesiculating membranes, thereby providing force for their constriction and scission (reviewed in Refs.…”
mentioning
confidence: 99%
“…The DNM2 molecule consists of five functional domains: an N-terminal catalytic domain; a so-called "middle domain" implicated in dynamin-dynamin interactions; a PH domain involved in phosphoinositide binding; a GTPase effector domain, which interacts with the catalytic domain and stimulates its GTPase activity; and a C-terminal proline/arginine-rich domain, which mediates interactions of dynamin with other proteins. Most of the currently known CNM-associated dynamin mutations are located in the middle and PH domains (4,13), but others have recently been identified in the GTPase effector domain (3,14).…”
mentioning
confidence: 99%
“…The disease is a result of mutations of genes associated with intracellular trafficking (Szigeti and Lupski, 2009;Durieux et al, 2010). Mutations in DNM2 result in CMT.…”
Section: Cmt and Cnmmentioning
confidence: 99%